รูปแบบการพัฒนาคุณภาพและมาตรฐาน ในการให้บริการสุขภาพปฐมภูมิในจังหวัดสงขลา: Model for Developing Quality and Standards in Primary Health Care Services in Songkhla Province - นิลสุวรรณ, นิภาศ; ชวน มุณีแนม, ชวน มุณีแนม (วารสารวิชาการกรมสนับสนุนบริการสุขภาพ, 2025)
การวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนารูปแบบการยกระดับคุณภาพและมาตรฐานการให้บริการสุขภาพปฐมภูมิ ในจังหวัดสงขลา โดยใช้ระเบียบวิธีวิจัยแบบผสมผสาน กลมุ่ ตัวอย่างเชิงปริมาณประกอบด้วยผ้บู ริหาร แพทย์ พยาบาล เจ้าหน้าที่สาธารณสุข และประชาชนผู้รับบริการ จำนวน 400 คน ส่วนกลุ่มตัวอย่างเชิงคุณภาพจำนวน 20 คน คัดเลือกแบบเจาะจงจากผู้บริหารระดับอำเภอ–จังหวัด และหัวหน้าหน่วยบริการปฐมภูมิที่มีประสบการณ์ ด้านสาธารณสุขอย่างน้อย 5 ปี การวิจัยดำเนินตาม 3 ขั้นตอน ได้แก่ การวิเคราะห์บทบาทและสมรรถนะ การประเมินความต้องการสมรรถนะ และการสัมภาษณ์เพื่อออกแบบรูปแบบสมรรถนะที่เหมาะสมกับบริบทพื้นที่ ผลการวิจัยเชิงปริมาณพบว่า คุณภาพการบริหารจัดการโดยรวมอยู่ในระดับสูง (Mean = 4.21, SD = 0.63) โดยเฉพาะการสื่อสารภายในและการถ่ายทอดนโยบาย การจัดสรรทรัพยากรอยู่ในระดับปานกลาง (Mean = 3.45, SD = 0.72) สะท้อนปัญหาการขาดบุคลากรเฉพาะทางและข้อจำกัดด้านงบประมาณ ระบบการส่งต่อมีระดับปานกลางค่อนไปทางต่ำ (Mean = 3.18, SD = 0.81) จากปัญหาการเชื่อมโยงข้อมูลระหว่างหน่วยบริการ ขณะที่ความพึงพอใจของประชาชนอยู่ในระดับสูง (Mean = 4.32, SD = 0.58) ผลการวิจัยนำไปสู่การพัฒนารูปแบบสมรรถนะ 4 ด้าน ได้แก่ ภาวะผู้นำ การประสานงาน การใช้ข้อมูลตัดสินใจ และการบริหารจัดการเชิงระบบ พร้อมข้อเสนอแนะ ให้เสริมสร้างศักยภาพบุคลากร พัฒนาระบบข้อมูลและการติดตามประเมินผล รวมทั้งเพิ่มการมีส่วนร่วมของประชาชนเพื่อยกระดับคุณภาพบริการปฐมภูมิอย่างยั่งยืน This study aimed to develop a competency-based model to enhance the quality and standards of primary healthcare services in Songkhla Province, Thailand. A mixed-methods research design was employed. The quantitative sample consisted of 400 participants, including frontline administrators, physicians, nurses, public health officers, and service users in primary care units (PCUs). The qualitative sample comprised 20 purposively selected district- and provincial-level administrators and PCU leaders with at least five years of experience in public health management. The research process involved three main stages: analyzing roles and competencies of primary care personnel, assessing competency needs, and conducting in-depth interviews to design a context-appropriate competency model. Quantitative findings showed that overall management quality was rated at a high level (Mean = 4.21, SD = 0.63), particularly in internal communication and policy dissemination. Resource allocation was rated moderate (Mean = 3.45, SD = 0.72), reflecting shortages of specialized personnel and budget constraints. The referral system scored moderately low (Mean = 3.18, SD = 0.81) due to limited information linkage between service levels. User satisfaction was high (Mean = 4.32, SD = 0.58), especially regarding staff competencies and interpersonal skills. The study resulted in the development of four key competency domains: leadership, coordination, data-driven decision-making, and systems management. Recommendations include strengthening personnel capacity, improving health information systems, enhancing monitoring and evaluation mechanisms, and promoting community participation to sustainably improve the quality of primary healthcare services.